INFLUENCE OF POLISHING SYSTEM ON COLOR CHANGES FOR A NANOIONOMER RESTORATIVE MATERIAL AFTER IMMERSION IN A COFFEE-BASED SOLUTION - HERDA, ELLYZA; AKA, PUTRA; TRIAMININGSIH, SITI (International Journal of Applied Pharmaceutics, 2019)
Objective: In this study, we aim to assess a polishing system’s influence on the color change of a nanoionomer after immersion in a coffee-based solution. Methods: The specimens were divided into four groups, of which three of them were polished using Sof-Lex XT, PoGo, or OptraPol. However, the samples in the fourth group were unpolished. The color was then determined using a spectrophotometer and color changes were evaluated using a CIELAB system. The data were analyzed using one-way ANOVA and paired samples t-test systems. Results: While the lightness (L*) value significantly decreased (p<0.05) after the polishing procedure, the red-green coordinate (a*) and yellow-blue coordinate (b*) values did not show any significant change for any of the groups. The samples that were polished using OptraPol demonstrated the smallest color change after polishing; moreover, for this group, the color changes were significantly different from those that were observed for PoGo and Sof-Lex XT groups. After immersing into a coffee-based solution, there were significant changes observed for the L*, a*, and b* values (p<0.05) for all the groups that were studied. Importantly, the color changes that were observed for the OptraPol group were not statistically significant compared to those that were observed for PoGo and the unpolished groups. Conclusion: The immersion of unpolished and polished nanoionomers in a coffee-based solution will result into color changes and the smallest variations, in this case, occurred for the nanoionomer that was polished using OptraPol.